Problems of the treatment of pneumonia caused by pseudomonas aeruginosa - V. A. Mochonyi; O. A. Savchenko; S. L. Podsevakhina; O. V. Tkachenko (Сучасні медичні технології)
Pseudomonas infection is one of the most problematic pathogens of pneumonia, because it has natural resistance to many antibiotics, is able to quickly form acquired resistance, often causes severe pneumonia with a poor prognosis. Analysis of the literature data showed that today P. Aeruginosa demonstrates resistance to all anti-pest control antibiotics, with the exception of polymyxin. The levels of resistance of P. Aeruginosa are very considerably depending on the region of the survey and the profile of the hospital, which requires monitoring the sensitivity of microorganisms in each department of the hospital. The data on the degree of resistance to P. Aeruginosa antibiotics in Ukraine are limited, but available local studies on this issue also show a high level of resistance of this microorganism to the main anti-pest antibiotics. In patients with pneumonia and risk factors for the involvement of Pseudomonas infection, most authors recommend combination antibiotic therapy, which has a synergistic effect on P. Aeruginosa, which allows, in most cases, to overcome the resistance of this microorganism. According to the literature, such synergism has been proven for the combination: beta-lactams (ceftazidime, cefepime, antipseudomonas carbapenems) + aminoglycosides (amikacin) or fluoroquinolones (ciprofloxacin or levofloxacin). The use of these drugs in the maximum allowable dose allows a higher degree of probability to achieve the eradication of P. Aeruginosa in patients with pneumonia and to improve the prognosis for this disease.